Hiperestesia espinhal focal como fator prognóstico em cães paraplégicos sempercepção de dor profunda - Wrzesinski, Mathias Reginatto (2021)
Intervertebral disc extrusion (IVDE) is the most common cause of compressive injury in spinal cord of dogs, whose prognosis is variable and depends on several factors, being the perception of deep pain (PDP) considered the main parameter. Studies on new prognostic factors are assessed in order to assist more accurate estimate of functional recovery. Therefore, the objective of study was to evaluate whether spinal hyperesthesia (SH), at the site of compression, can be used as a prognostic factor for functional recovery of dogs with acute extrusion of intervertebral disc (Hansen type I), without presence of PDP undergoing thoracolumbar hemilaminectomy. Among 68 dogs included in this retrospective study, 73.5% (50/68) shown SH and, in 26.5% (18/68) pain was not identified. Recovery was satisfactory in dogs with SH in 60% (30/50) and, without SH, in 27.7% (5/18) of all cases, indicating that paraplegic dogs without PDP, but with presence of spinal hyperesthesia, have 2.2 times more chance of recovery when compared to dogs of the same condition, but without SH. No studies were found that evaluated an SH measuring palpation of the spine as a prognostic factor, which reinforces the relevance of the present study. The results of this work imply that SH in paraplegic dogs affected by thoracolumbar IVDE, without the presence of PDP, can be used as a possible prognostic indicator of functional recovery.